KEPEMIMPINAN KEPALA MADRASAH DALAM PENERAPAN KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI MADRASAH ALIYAH SWASTA IHYA ULUMUDDIN KABUPATEN KAIMANA - Hardi (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2025)
This study aims to examine the process, supporting and inhibiting factors, and the impact of the principal’s leadership in the implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) subjects at Ihya Ulumuddin Private Madrasah Aliyah in Kaimana Regency. Using a descriptive qualitative approach, data were collected through in-depth interviews with one principal, one PAI teacher, one class teacher, two parents, and one education figure in Kaimana. Data analysis was conducted systematically to identify leadership patterns, internal and external factors affecting curriculum implementation, and its impact on PAI learning. The results show that the principal applies a transformational-participative leadership style that supports the empowerment of teachers and students; supporting factors include the commitment of young teachers, technological support, and parental cooperation, while inhibiting factors include limited training for senior teachers, suboptimal ICT infrastructure, and resistance to change. In terms of impact, the implementation of the Merdeka Curriculum in PAI has led to increased student learning independence, project-based learning innovations, and improved school–community relationships, although disparities between senior and junior teachers still exist. This study recommends strengthening principal leadership training, improving ICT facilities, and establishing internal teams for sustainable curriculum implementation.